DEMOCRATIC IN ENSURING HUMAN DIGNITY THE ROLE OF VALUES (Scientific journal of the Fergana State University, 2026)
In this article, during the development of human society, spiritual culture has been improved through actions, connections, and relationships between people. Modern teachings about man, on the one hand, are a creative continuation of previous views, and on the other hand, determine the theoretical, methodological, and practical aspects of historical development and show its prospects. In the context of globalization, the teachings about man are extremely diverse, consisting of alternative teachings, on the one hand, complex-systemic research, and on the other hand, from the "ocean of teachings" to enhance the spiritual development of man, to strengthen the idea of national independence, to understand objective truth, to what extent it meets the requirements of the time.